A framework for evaluation and control of the factors that influence the software process improvement in small organizations. Issue 4 (23rd September 2011) - Espinosa‐Curiel, Ismael Edrein; Rodríguez‐Jacobo, Josefina; Fernández‐Zepeda, José Alberto; Biró, Miklós; Messnarz, Richard; Palacios, Ricardo Colomo
SUMMARY Today, many micro‐sized and small‐sized software enterprises (MSEs) have initiated a software process improvement (SPI) initiative to be more competitive in the software market. SPI initiatives in MSEs have not been entirely successful; in general, MSEs consider them a long, expensive, and difficult activity. One of the reasons of these results is that a large number of human, social, technical, and organizational factors influence these initiatives. MSEs require to control, mitigate, or solve these factors to succeed in their initiatives. However, because there is a lack of information regarding the characteristics and behavior of these factors in the context of the MSEs, SPI managers have limited information to design strategies to control these factors. This work proposes a framework of factors that influence SPI initiatives in MSEs and a methodology to evaluate and control these factors. This framework includes 132 factors grouped in six categories. Additionally, we specify their properties, their value scales, and the property values for each factor. SPI managers could use this framework to evaluate and control potential threats to SPI initiatives and to propose better SPI strategies. Copyright © 2011 John Wiley & Sons, Ltd.